Replication Strategies for Distributed IEC 61499 Applications - Santos, Adriano A (2018)
The IEC 61499 standard defines a framework for the development of distributed control applications, including a modeling language and its associated execution semantics. Traditionally industrial control applications run on a single computing device. When moving to a distributed solution new failure models need to be taken into account. In previous work the authors have this proposed a framework to support the development of fault tolerant distributed IEC 61499 applications, based on the use of active replicas. Special communication protocols were considered in order to guarantee replica determinism and synchronization. In this paper we relax the replica determinism requirement and explore other possible implementations for the replication framework that do not require special communication protocols and are easier to implement in practice.